Wintersweet Branch‐Like C/C@SnO2/MoS2 Nanofibers as High‐Performance Li and Na‐Ion Battery Anodes. (9th November 2017) - Zhou, Huimin; Xia, Xin; Lv, Pengfei; Zhang, Jin; Pang, Zengyuan; Li, Dawei; Cai, Yibing; Wei, Qufu
Abstract: Structure and morphology of molybdenum disulfide (MoS2 ) play an important role in improving its reversible lithium storage and sodium storage as anodes. In this study, a facile method is developed to prepare C/C@SnO2 /MoS2 nanofibers with MoS2 nanoflakes anchoring on the core–shell C/C@SnO2 nanofibers through hydrothermal reaction. By adjusting the concentration of MoS2 precursors, the synthesized MoS2 with different slabs dimensions, size, and morphologies are obtained, constituting budding and blooming wintersweet branch‐like composite structure, respectively. Owing to scattered MoS2 nanoparticles and sporadic MoS2 nanoflakes, the budding wintersweet branch‐like composite nanofibers processes less slabs of staking in number and large specific surface area. Benefiting from the exposed C@SnO2 shell layer, the synergistic effect among SnO2, carbon, and MoS2 is strengthened, which maximizes the advantage of each material to exhibit stable specific capacities of 650 and 230 mAh g −1 for Li‐ion batteries and Na‐ion batteries after 200 cycles. Abstract : The budding wintersweet branch‐like C/C@SnO2 /MoS2 nanofibers provide better cycling performance as anodes for lithium‐ion batteries and sodium‐ion batteries than blooming structure composites. For the former, MoS2 nanoflakes combined with abundant MoS2 nanograins serve as surface sensitizers to boot the electrochemical properties of carbon‐rich nanofibers, where diverse reactive sites are provided and severe restaking of MoS2 is alleviate.